Development of plant regeneration system and agrobacterium-mediated transformation of Brassica oleracea L. subsp. italica cv. green marvel with HSP101 gene - Ravanfar, Seyed Ali (2012)
Broccoli seeds are among the most commonly imported vegetable seeds in Malaysia. In Malaysia due to the humid climate, production of hybrid seeds is almost impossible. Consequently, improvement of in vitro culture method for clonal propagation of broccoli plants having the F1 hybrid characteristics is essential. Broccoli plants respond adversely to extreme temperatures and high humidity in the lowland thus, gene transformation for heat tolerance would be beneficial. Cameron Highlands is the main broccoli producing area in Malaysia because of the suitable cool climate and the cultivar that is commonly grown is Green Marvel. Therefore, the main objectives of this study were to improve the shoot regeneration system for Brassica oleracea subsp. italica cv. Green Marvel and to introduce Arabidopsis thaliana HSP101 (Athsp101) cDNA into broccoli through Agrobacterium tumefaciens-mediated transformation in order to increase its heat-tolerance characteristic. Multiple shoot formation from hypocotyl and shoot tip explants were assessed using different concentrations of TDZ (thidiazuron), zeatin and kinetin. In the experiment on multiple shoot formation on hypocotyl explants, TDZ at 0.1 mg/l induced the highest percentage of explant with shoot (96.67%) and the highest mean number of shoots per explant (6.17). In the experiment on shoot multiplication from shoot tip explants, the highest percentage of shoot tip explant producing shoots (100%) was on medium with 0.1 mg/l TDZ followed 1.5 mg/l zeatin (96.67%), while, the highest number of shoots per explant (4.27) was on 1.5 mg/l zeatin. Therefore, 0.1 mg/l TDZ was considered the most suitable for adventitious shoot formation from hypocotyl explants and 1.5 mg/l zeatin from shoot tip. In the determination of minimum inhibitory concentration (MIC) of kanamycin for effective screening of broccoli transformants, the lowest percentage (0.0%) and mean number of survived hypocotyl explants (0.00) was on shoot regeneration medium (SRM) containing 60 mg/l kanamaycin, while the lowest percentage (0.0%) and mean number of survived shoot tip explants (0.00) occurred on SRM containing 90 and 100 mg/l kanamycin. Therefore, 50 mg/l and 80 mg/l kanamaycin were the chosen MIC for hypocotyl and shoot tip explants, respectively. In the optimization of factors affecting Agrobacterium mediatedtransformation of broccoli with AtHSP101 gene and the regeneration of putative transformed plantlets, hypocotyls explants precultured on SRM with 200μM acetosyringone produced the highest percentage (13.33 %) and mean number of putative transformants (0.17), while shoot tip explants precultured on callus induction medium (CIM) with 200μM acetosyringone produced the highest percentage (23.33%) and mean number of putative transformants (0.27) after 8 weeks of culture. Optimization of bacterial dilution and inoculation time showed that the inoculation of hypocotyl segments in 1:5 bacterial dilution for 30 min produced the highest percentage (20 %) and mean number (0.27) of putative transformants. The same bacterial dilution and inoculation time also produced the highest percentage (30%) and mean number (0.33) of putative transformant from shoot tip explants. Thus, preculture with 200μM acetosyringone followed by inoculation in (1:5) bacterial dilution for 30 min was the most successful for transformation of broccoli with AtHSP101 gene. PCR analysis showed the expected fragment size of the AtHSP101 gene, while Southern blot analysis showed different hybridization bands in the hypocotyl (1 and 2 gene copy number) and shoot tip (3 gene copy number) derived transformants. The gene expression was confirmed through reverse transcriptase (RT-PCR) assay.Consequently, the transgenic broccoli plantlets were transferred to different temperature regimes (20ºC, 30ºC and 34ºC) in the transgenic greenhouse to evaluate the efficacy of HSP 101 gene in increasing their heat tolerance. Results showed that the transgenic plants could survive and performed normally, producing flower heads even at the highest tested temperature of 34ºC. In conclusion, an improved regeneration system has been established from hypocotyl and shoot tip explants of broccoli followed by successful transformation with AtHSP101 for resistance to high temperature.